Coconut husk fibre reinforced polypropylene composite / Syahrul Azli Abd Aziz - Abd Aziz, Syahrul Azli (2008)
Polypropylene composite were formulated by using coconut husk fiber. The potential of CHF as reinforcement fiber in the plastic composite has been investigate and the affect on the mechanical properties was studied by using universal testometric and impact test machine. The effect of the maleic anhydride as coupling agent in the PP/CHF composite was studied. The composites were also characterized by using FTIR and the morphology of the PP/CHF composite was studied by using SEM. It was found that tensile strength and the impact strength of the PP/CHF reduced as the increased of the fiber loading but PP/CHF treated with maleic anhydride composite results in increased of the impact strength but decrease of the tensile strength with the increased of fiber loading. Furthermore, the Young's modulus increased when the percentage of fiber loading increased.